Physical Properties of Latvian Hemp Fibres (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Each year more and more people focus on healthy, ecological and environmental-friendly living. Environmentally friendly lifestyle doesn’t mean that we are using only natural products, but attention is pointed to the manufacturing and production process also. The rapid development of recycled and biodegradable products causes expanding usage of hemp fibers both in household and technical textiles. The analysis of hemp cultivation and usage trends in the world and Europe shows that hemp cultivation and processing in Latvia has good perspectives. Product quality is influenced by raw materials. In this case it is hemp fiber descriptive characteristics. Hemp fibers are natural fibers and their properties varies according to plant growing regional climatic conditions, amount of manure, plant density, harvesting time and pre-treatment technological processes. There are studied the influence of above mentioned factors on chemical composition, geometrical and physical properties of the Latvian hemp fiber both local and foreign cultivars. The work was carried out in cooperation between Riga Technical University, Textile Technology and Design Institute and the Agriculture Science Centre of Latgale.